The Value of Passenger Car Equivalent using the Time Headway Method on Urban Roads - Irwandi Irwandi; Anastasia Caroline Sutandi; Elsa Tri Mukti (Civil Engineering Dimension, 2025)
The escalating proliferation of vehicles has had a significant impact on the existing Passenger Car Equivalent (PCE) values, making them less effective under current traffic conditions for assessing road performance. This study aims to redefine PCE values for urban highways using the Time Headway method. Data collection was conducted over four days during peak traffic hours. The methodology involved direct field observations, analysis footage, and statistical modeling of time headway data distributions. The Kolmogorov-Smirnov fit test identified the Wakeby distribution as the most suitable representation of time headway data. Results yielded PCE values of 0.413 for motorcycles and 1.416 for medium vehicles, with discrepancies of 65.37% and 18.02%, indicating that the measured PCE values surpass the established benchmarks. The rise in vehicle numbers and the methodologies employed contribute to the variations in observed PCE levels. This research provides valuable insights for urban road planning and foundation studies for future research.